Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan Air Mineral Alfamart Pada Toko Alfamart Cabang Cikokol - Mada Faisal Akbar; Hadion Wijoyo; Adhi Wibowo (Mahesa Research Center, 2021)
Alfamart is also one of the mini market stores in Indonesia which also applies the importance of providing the best service for each customer and always tries to understand the products that its customers need and want. By offering various kinds of bottled water products, Alfamart strives to satisfy and provide convenience to each of its customers in making purchase transactions. In this study, researchers used a saturated sampling technique in determining the number of samples. Based on the number of population and the sampling technique used, the number of samples in this study was 75 respondents. Based on the results of the distribution of product quality instruments (x) to 75 Alfamart mineral water customers, it shows that, product quality (x) in mineral water, customer loyalty (y) for mineral water at Alfamart Cikokol Tangerang Branch is currently good. The effect of product quality on customer loyalty of Alfamart mineral water at Alfamart store Cikokol Tangerang branch shows that, the simple linear regression equation Y = 15.42 + 0.39. (x) means that this equation can estimate / calculate the effect of product quality (x) on customer loyalty (y). If the product quality (x) is increased one-by-one, customer loyalty (y) will increase to 0.39 and if the product quality is increased to 10 then customer loyalty will increase to 3.9. The coefficient of determination of the product quality variable (x) contributed 41.90% to the customer loyalty variable (y) at Alfamart Stores Cikokol Tangerang branch. In the hypothesis test t count 7,256 t table 1,993, thus this study proves that